Macroeconomic and Distributional Impacts of Jatropha-based Biodiesel in Mali - Boccanfuso, Dorothee; Coulibaly, Massa; Timilsina, Govinda R.; Savard, Luc (World Bank, Washington, DC, 2013)
Mali, a landlocked West African nation at the southern edge of the Sahara Desert, has introduced a program to produce biodiesel using jatropha curcas, a non-edible shrub widely available throughout the country by farmers for generations as a living fence for their gardens. The aim of the program is to partially substitute diesel, which is entirely supplied through imports, with domestic biodiesel produced from a feedstock that does not have any commercial value otherwise and thus has zero opportunity cost. This paper uses a computable general equilibrium model to investigate economy-wide and distributional impacts of large-scale jatropha production on different types of lands, and conversion of jatropha oil to biodiesel for domestic consumption. It assesses impacts on agricultural and other commodity markets, resource and factor markets, and international trade. The results are fed into a detailed household survey-based micro-simulation model to assess impacts on poverty and income distribution. The study finds that the expansion of jatropha farming would be beneficial in terms of both macroeconomic and distributional impacts as long as idle lands, which have been neither used for agriculture nor protected as forests, are utilized. However, if jatropha plantation is carried out on existing agriculture lands, the economy-wide impacts would be negative although it would still help reduce rural poverty.